Investigation of the hydrophobic recovery of He-plasma treated polyimide using ion shower system - Go, Arlene Kris C. (2012)
Plasma treatment has proven to be an effective technique in surface modification of polymer surfaces. Surface modification can induce an increase in the hydrophilic property of the surface to ensure good wettability and adhesion. However, plasma modified polymer surfaces is unstable and has a high tendency to undergo hydrophobic recovery. This study investigates the effects of plasma parameters namely accelerating voltage, treatment time and accelerating voltage on the rate of hydrophobic recovery of He-plasma treated Kapton polyimide surfaces. Possible effects of interaction of the parameters were also considered. Ageing of the plasma treated polyimide samples with air was done for 30 days. Wetting characteristic of the plasma treated and aged surface were evaluated using contact angle analysis while changes in the functional groups present at the surface after 15-days ageing were assessed using FTIR analysis. Adhesion characteristics of the polyimide samples with metal were evaluated using peel testing and pull-off testing. Contact angle results suggest that polyimide surfaces exhibit a two-step hydrophobic recovery. First step corresponds to a rapid linear increase in the rate of hydrophobic recovery for 45 minutes after which, a slow increase in the rate of hydrophobic recovery was observed up to 30 days. For the first stage, increase in accelerating voltage will increase the rate of hydrophobic recovery while increase in treatment time and chamber pressure will generally cause a decrease in the rate of hydrophobic recovery. However, ANOVA results suggest that rate of hydrophobic recovery is highly dependent on the interaction effects of the parameters. For the second stage of hydrophobic recovery, accelerating voltage and chamber pressure were found to be statistically significant as well as effects of two factor interactions AC (accelerating voltage-chamber pressure) and BC (exposure time-chamber pressure). Similar trends of effects of parameters were obtained for the first and second stage of hydrophobic recovery except that for the second stage, high setting of the chamber pressure leads to a slower rate of hydrophobic recovery with increase in accelerating voltage. FTIR analysis supports the result of the contact angle analysis where treatment combinations A, AB and AC, having the highest computed slop, has the lowest intensity absorbance peaks for C=O and C-O. Hydrophobic recovery mechanism of the polyimide surface appears to be reorientation of the polar groups away from the surface leading to fast hydrophobic recovery. A parabolic relationship is obtained between energy delivered to the surface and computed slope. A critical energy level at about 2.5kJ exists where maximum hydrophobic recovery mechanism occurs after which the rate of hydrophobic recovery is slower. From peel testing, plasma-treated aged samples exhibited the smallest % area peeled off during peel testing at 3%. Pull-off test result for the aged samples showed that delamination occurs at polyimide substrate to glass slide interface. The metal coating on the polyimide film remained intact after pull-off test on plasma treated samples, as-treated or aged. Peel-off and pull-off tests suggest that aged samples have the best adhesive characteristic compared to untreated and as-treated samples. From the results of the study, polyimide surfaces subjected to plasma treatment are relatively unstable and are prone to hydrophobic recovery. However, even after ageing, plasma-treated polyimide surfaces still exhibit good adhesion to silver metal coating.